2020
DOI: 10.1136/bmjopen-2019-033898
|View full text |Cite
|
Sign up to set email alerts
|

Using a machine learning approach to predict mortality in critically ill influenza patients: a cross-sectional retrospective multicentre study in Taiwan

Abstract: ObjectivesCurrent mortality prediction models used in the intensive care unit (ICU) have a limited role for specific diseases such as influenza, and we aimed to establish an explainable machine learning (ML) model for predicting mortality in critically ill influenza patients using a real-world severe influenza data set.Study designA cross-sectional retrospective multicentre study in TaiwanSettingEight medical centres in Taiwan.ParticipantsA total of 336 patients requiring ICU-admission for virology-proven infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 32 publications
1
70
0
1
Order By: Relevance
“…Our model had low bias with good generalizability and excellent discrimination (AUROC > 0.90). Although we found no direct comparison in the literature for sustained PARDS prediction, the AUROC for ARDS mortality in the literature ranges from 0.60 to 0.84 ( 8 13 , 17 , 43 ). Second, because many clinical variables are missing that limit the ability to diagnose PARDS, our study provides a clinically useful definition of AHRF that can be done using the available variables in clinical practice.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our model had low bias with good generalizability and excellent discrimination (AUROC > 0.90). Although we found no direct comparison in the literature for sustained PARDS prediction, the AUROC for ARDS mortality in the literature ranges from 0.60 to 0.84 ( 8 13 , 17 , 43 ). Second, because many clinical variables are missing that limit the ability to diagnose PARDS, our study provides a clinically useful definition of AHRF that can be done using the available variables in clinical practice.…”
Section: Discussionmentioning
confidence: 72%
“…Predictive models have been designed to predict ARDS ( 8 ) or its mortality ( 9 13 ). Nearly all published ARDS predictive models used logistic regression (LR), which is fairly easy to understand, but must follows several assumptions and has limited abilities to exploit nonlinear data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tree-based classifiers, including RF and XGBoost, based on homogeneity, fit the characteristics of the data set for the present study. We speculated that the application of regularization, using Taylor expansion to estimate the loss function, and high flexibility to allow for fine-tuning might enable XGBoost to perform better than RF [34]. Taken together, our findings suggested that the XGBoost approach can reflect the feature importance and set up a mortality prediction model with extreme accuracy.…”
mentioning
confidence: 84%
“…La comparación de los resultados obtenidos por técnicas convencionales con las obtenidas mediante un análisis avanzado con random forest (ML) da fortaleza a los hallazgos, y parece indicar que las nuevas técnicas serán capaces de añadir información a las técnicas de análisis clásico, pero gran parte de la información sustantiva puede lograrse con estas últimas 7 . Eso sí, para que las técnicas de RL tengan consistencia debemos tener registros de calidad y de tamaño muestral suficiente, lo que se ha garantizado en este estudio, a diferencia de otros recientes en los que un tamaño muestral insuficiente potencia la capacidad predictiva del ML sobre la RL 8 .…”
unclassified